Muslim communities in contemporary Netherlands - De Ruiter, Jan Jaap (UIN Sunan Ampel Surabaya, 2024)
This contribution aims to give an overview of the position of Muslim communities in the Netherlands. The approach is driven by the question of the processes of acculturation of the mentioned communities in the Netherlands, the concept of acculturation as understood by Sam & Berry (2010). The article is composed as follows. Section 1 draws the theoretical context of this article and formulates a main research question. Section 2 presents some statistical data on the Muslim communities in the country; section 3 presents a sketch of the communities under concern, treating divers aspects; section 4 presents a selection of studies on acculturation processes of Muslims in the Netherlands. Section 5 then wraps up the findings and observations and concludes with the presentation of an answer to the key question of this article, and a discussion.